MEASURING AIR AND TERRESTRIAL TRANSPORT COMPANY REPUTATION: TOURISM INTANGIBLES EXPRESSED IN THE DIGITAL ENVIRONMENT - M. Q. Ramos, Célia; Casado-Molina, Ana M.; I. Peláez, José (Journal of Tourism, Sustainability and Well-being, 2017)
The reputation of companies within the transport industry is influenced by competitive dynamics within the sector: low-cost flights, the attractiveness of destinations, online user-generated content about users’ experiences, and more. At the same time, social media provides a means for companies to manage issues of tourism intangibles. Thus, it is relevant to analyse transport reputation in the digital environment, taking into consideration the resources for managing these intangibles. This paper presents a method for measuring transport reputation based on an analysis of tourism consumers’ digital opinions and passengers’ comments about their experiences with these firms. The use of social media, such as TripAdvisor and Facebook, conjugated with business intelligence tools and complemented by data mining techniques, can contribute to the development of metrics that consider intangibles like emotions and experiences, with the aim of measuring, analysing, and visualizing the complex relationships between these intangibles and transport companies’ reputations. The results present the impacts of these intangibles through clusters and positioning maps focusing on these issues. This investigation contributes to our knowledge about airlines and terrestrial transport companies that seek to differentiate their positioning in tourism markets through their reputations.